Emotional distractors and attentional control in anxious youth: eye tracking and fMRI data. Issue 1 (2nd January 2021) - Smith, Ashley R.; Haller, Simone P.; Haas, Sara A.; Pagliaccio, David; Behrens, Brigid; Swetlitz, Caroline; Bezek, Jessica L.; Brotman, Melissa A.; Leibenluft, Ellen; Fox, Nathan A.; Pine, Daniel S.
ABSTRACT: Attentional control theory suggests that high cognitive demands impair the flexible deployment of attention control in anxious adults, particularly when paired with external threats. Extending this work to pediatric anxiety, we report two studies utilising eye tracking (Study 1) and functional magnetic resonance imaging (Study 2). Both studies use a visual search paradigm to examine anxiety-related differences in the impact of threat on attentional control at varying levels of task difficulty. In Study 1, youth ages 8–18 years ( N = 109), completed the paradigm during eye tracking. Results indicated that youth with more severe anxiety took longer to fixate on and identify the target, specifically on difficult trials, compared to youth with less anxiety. However, no anxiety-related effects of emotional distraction (faces) emerged. In Study 2, a separate cohort of 8–18-year-olds ( N = 72) completed a similar paradigm during fMRI. Behaviourally, youth with more severe anxiety were slower to respond on searches following non-threatening, compared to threatening, distractors, but this effect did not vary by task difficulty. The same interaction emerged in the neuroimaging analysis in the superior parietal lobule and precentral gyrus-more severe anxiety was associated with greater brain response following non-threatening distractors. Theoretical implications of these inconsistent findings are discussed.